2019
DOI: 10.4103/ajns.ajns_67_19
|View full text |Cite
|
Sign up to set email alerts
|

A case series of craniopharyngioma: Epidemiological study and management analysis at tertiary care center

Abstract: Introduction:Debate continues as to the optimal treatment for craniopharyngioma; radical surgical resection or partial resection followed by radiotherapy. Radical surgical resection may be complicated by intraoperative injury to surrounding structures and stormy postoperative hormonal problems. This study aims to examine the result of safe maximal surgical resection.Methodology:Retrospective study of all histopathologically proven craniopharyngiomas who had undergone surgical resection over an almost 4-year pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some studies investigating the onset of disturbances and the outcome of CP patients have reported the occurrence of sleep disturbances; however, without providing any assessment and characterization ( 28 , 31 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies investigating the onset of disturbances and the outcome of CP patients have reported the occurrence of sleep disturbances; however, without providing any assessment and characterization ( 28 , 31 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…7,8 The two peaks in the age distribution of the tumor reported in literature show <10 and >50 years of age. 1,5,7,9,10 The most commonly presenting symptoms are vision disturbances, high intracranial pressure and endocrine manifestations related to the dysfunction of hypothalamus and/or pituitary gland. 1,2,4,5,7,8,9 It is rarely reported during the fetal life with a scant published data in the neonatal period.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,7,9,10 The most commonly presenting symptoms are vision disturbances, high intracranial pressure and endocrine manifestations related to the dysfunction of hypothalamus and/or pituitary gland. 1,2,4,5,7,8,9 It is rarely reported during the fetal life with a scant published data in the neonatal period. We present the case of a patient who got diagnosed with the supra-sellar tumor on prenatal ultrasound and had surgical resection after birth showing tooth-like enamel structures on a histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Craniopharyngiomas (CPs) (cranio = skull, pharynx = throat, and omatumour) are slow growing benign tumours arising from the squamous epithelial remnants of Rathke's pouch in the sellar/suprasellar region of the brain [229][230][231]. CPs originate along the path of the hypophyseal-pharyngeal duct (craniopharyngeal duct) [232], however, they can extend anywhere from the nasopharynx to the tuber cinereum and may also arise within the sphenoid bone, the sella, or the suprasellar region [229].…”
Section: Craniopharyngiomasmentioning
confidence: 99%